EFEKTIVITAS PROGRAM BANTUAN RUMAH SEHAT LAYAK HUNI (RSLH) ( STUDI KASUS DI DESA BUKIT GAJAH KECAMATAN UKUI KABUPATEN PELALAWAN) - Helda Yanti; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The fulfillment of housing needs is the right of every citizen, because it is guaranteed by the 1945 Constitution in Article 28H Paragraph 1 which states that